Associação do alisquireno e L-arginina melhora a atividade simpática e função renal na hipertensão renovascular - Tiradentes, Renata Viana (2015)
Renovascular hypertension is characterized by increased renal sympathetic activity, angiotensin II, and by endothelial dysfunction. The purpose of this study was to determine the role of renal sympathetic nerve activity (RSNA) in mediating the anti-hypertensive effects of aliskiren (ALSK) and L-arginine (L-ARG) in a rat renovascular hypertension model. Hypertension was induced by clipping the right renal artery, and the following 5 groups were divided: Sham operated; 2-kidney, 1-clip (2K1C); 2K1C plus ALSK; 2K1C plus L-ARG; and 2K1C plus ALSK+ L-ARG. The systolic blood pressure (SBP) of 2K1C rats increased from 114.4±5.2 to 204±12.7 mmHg, (P< 0.05) and was only reduced by ALSK+L-ARG treatment (138.4±4.37 mmHg). The 2K1C hypertension increased the baseline RSNA (SHAM: 62.4±6.39 vs 2K1C: 97.4±8.43%). L-ARG or ALSK+L-ARG treatment significantly decreased baseline RSNA (2K1C L-ARG:70.7±2.39; 2K1C ALSK+L-ARG: 69.3±4.23%), but ALSK treatment alone did not (2K1C ALSK: 84.2±2.5%). Urinary water, Na+ , Cl- and urea excretion were similar in the 2K1C L-ARG, 2K1C ALSK+L-ARG and SHAM groups. The combination of ALSK+L-ARG restored urine flow and increased the glomerular filtration rate. The nNOS expression in the non clipped kidney was significantly increased in 2K1C ALSK+L-ARG rats. In conclusion, combined ALSK+L-ARG treatment normalizes SBP and prevents renal dysfunction in 2K1C hypertensive rats, an effect that can be partially attributed to reduced RSNA.